Metabolite Biomarkers of Leishmania Antimony Resistance (2021)
ABSTRACT: Leishmania parasites cause leishmaniasis, one of the most epidemiologically important neglected tropical diseases. Leishmania exhibits a high ability of developing drug resistance, and drug resistance is one of the main threats to public health, as it is associated with increased incidence, mortality, and healthcare costs. The antimonial drug is the main historically implemented drug for leishmaniasis. Nevertheless, even though antimony resistance has been widely documented, the mechanisms involved are not completely understood. In this study, we aimed to identify potential metabolite biomarkers of antimony resistance that could improve leishmaniasis treatment. Here, using L. tropica promastigotes as the biological model, we showed that the level of response to antimony can be potentially predicted using 1H-NMR-based metabolomic profiling. Antimonyresistant parasites exhibited differences in metabolite composition at the intracellular and extracellular levels, suggesting that a metabolic remodeling is required to combat the drug. Simple and timesaving exometabolomic analysis can be efficiently used for the differentiation of sensitive and resistant parasites. Our findings suggest that changes in metabolite composition are associated with an optimized response to the osmotic/oxidative stress and a rearrangement of carbon-energy metabolism. The activation of energy metabolism can be linked to the high energy requirement during the antioxidant stress response. We also found that metabolites such as proline and lactate change linearly with the level of resistance to antimony, showing a close relationship with the parasite’s efficiency of drug resistance. A list of potential metabolite biomarkers is described and discussed.